Integrating deep learning in Pancasila education: evaluating the ‘Tugas Mulia Sila’ comic in elementary schools - Devy Yuliastri Kurnia Putri; Triyanto Triyanto; Deni Zein Tarsidi (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
Pancasila education in Indonesian elementary schools remains predominantly teacher-centered, limiting students' opportunities to internalize values through meaningful learning experiences. Although educational comics have been widely explored as instructional media, little empirical evidence exists regarding their integration with the four pillars of deep learning, integrative, mindful, meaningful, and joyful, as a unified framework for value-based learning. This study evaluates the practicality, student responses, and learning effectiveness of the Tugas Mulia Sila comic designed to support deep learning in fifth-grade Pancasila education. A mixed-method study employing a concurrent embedded design was conducted with 30 fifth-grade students, one classroom teacher, and two external observers at an Indonesian public elementary school. Quantitative data were collected through practical observations, student response questionnaires, and pretest–posttest assessments, while qualitative data were obtained through classroom observations and teacher interviews. Quantitative data were analyzed using descriptive statistics and normalized gain (N-gain), whereas qualitative findings were analyzed using the interactive model of Miles, Huberman, and Saldaña. The comic demonstrated high practicality (94%), while student responses across the four deep learning pillars were consistently positive (95%). Students' learning outcomes improved substantially, with an average N-gain of 0.69, indicating moderate-to-high learning effectiveness. The findings demonstrate that value-based comics can simultaneously operationalize integrative, mindful, meaningful, and joyful learning while improving students' understanding of Pancasila values. This study contributes an empirical framework for evaluating deep learning-based instructional media and offers practical implications for strengthening value education in elementary schools.